Blogs as Elusive Ethnographic Texts: Methodological and Ethical Challenges in Qualitative Online Research. Issue 1 (27th April 2017) - Kurtz, Liza C.; Trainer, Sarah; Beresford, Melissa; Wutich, Amber; Brewis, Alexandra
Burgeoning online environments offer completely new opportunities for ethnographic and other forms of qualitative research. Yet there are no clear standards for how we study online texts from an ethnographic perspective. In this article, we identify barriers to the application of traditional qualitative methods online, using the example of a systematic thematic analysis of weight-loss blogs. These barriers include the influence of the technology structuring online content, the fluid nature of online texts such as blogs, and the highly connected and public nature of online identities, which may span multiple social media platforms. We discuss some potential approaches to addressing these challenges as preliminary steps toward developing a tool kit suited to ethical, high-quality online modes of ethnographic research.